CT features of gastrointestinal spindle cell, epithelial, and round cell tumors in 41 dogs. Issue 2 (16th November 2022) - De Magistris, A.V.; Rossi, F.; Valenti, P.; Anson, A.; Penninck, D.G.; Agut, A.; Specchi, S.
Abstract: There is sparse published information on computed tomographic (CT) characteristics of canine gastrointestinal tumors. The purposes of this multi‐center, retrospective, descriptive study were to describe the CT features of histologically‐confirmed canine gastrointestinal spindle cell, epithelial, and round cell tumors and, when available, describe the corresponding ultrasound findings. The inclusion criteria were as follows: availability of pre‐and post‐contrast CT study, and a histopathological diagnosis of the lesions. Recorded parameters were tumor size, location, gastrointestinal wall layers involvement, lesion's growth and enhancement patterns, tumor margination, presence of stenosis, mineralization, ulcerations, lymphadenopathy, or other lesions in the abdomen/thorax. When available, ultrasound images were evaluated. Forty‐one dogs met the inclusion criteria and had the following histological diagnoses: 21/41 (51%) spindle cells (7 leiomyomas, 14 leiomyosarcomas/gastrointestinal stromal tumors (GISTs)), 13/41 (32%) epithelial (adenocarcinoma), and 7/41 (17%) round cell (lymphoma) tumors. The growth pattern was concentric, eccentric, and mixed in epithelial, spindle cell, and round cell tumors, respectively. Spindle cell tumors had the largest main volume and involved the outer gastrointestinal layer with an unaffected inner layer. Leiomyosarcomas/GISTs showed irregular margins compared to leiomyomas. Only lymphomas showed multifocal gastrointestinal involvement. Nine carcinomas and six spindle cell tumors caused partial stenosis with secondary sub‐obstruction. Mineralizations were more frequent in spindle cell tumors (10/21) and absent in lymphomas. Lymphadenomegaly was widespread in lymphomas, regional in leiomyosarcomas‐GISTs and adenocarcinomas, and absent in leiomyomas. The reported CT features may be useful in prioritizing the differential diagnosis between spindle cell, epithelial, and round cell tumors, similar to those reported on ultrasound.